2020
DOI: 10.37757/mr2020.v22.n4.14
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Vitamins and Homocysteine in Older Adults with Alzheimer Disease or Mild Cognitive Impairment in Cuba

Abstract: INTRODUCTION Age-related cognitive disorders, including Alzheimer disease, are among the main causes of disability and dependence in older adults worldwide. High blood homocysteine levels (hyperhomocysteinemia) are a risk factor for diseases whose metabolism involves different B vitamins. Antioxidant vitamins provide a protective effect by mitigating oxidative stress generated by these diseases. Epidemiological studies have presented varying results on the relationships between blood levels of these vitamins a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…Hypovitaminosis is implicated in the pathogenesis of various disorders [ 334 , 335 ], and there is increasing evidence that vitamins also play a key role in neurodegenerative diseases, leading to hypotheses concerning their use as disease biomarkers [ 336 , 337 ]. Regarding AD, although preliminary data are certainly encouraging, and the role of vitamins as biomarkers for AD has been widely investigated in literature ( Table 3 ) [ 188 , 297 , 338 , 339 , 340 , 341 , 342 , 343 , 344 , 345 , 346 , 347 , 348 , 349 , 350 , 351 ], some limitations in terms of consistency, reproducibility, and specificity remain to be solved, and further research is needed before hypothesizing a clinical application.…”
Section: Resultsmentioning
confidence: 99%
“…Hypovitaminosis is implicated in the pathogenesis of various disorders [ 334 , 335 ], and there is increasing evidence that vitamins also play a key role in neurodegenerative diseases, leading to hypotheses concerning their use as disease biomarkers [ 336 , 337 ]. Regarding AD, although preliminary data are certainly encouraging, and the role of vitamins as biomarkers for AD has been widely investigated in literature ( Table 3 ) [ 188 , 297 , 338 , 339 , 340 , 341 , 342 , 343 , 344 , 345 , 346 , 347 , 348 , 349 , 350 , 351 ], some limitations in terms of consistency, reproducibility, and specificity remain to be solved, and further research is needed before hypothesizing a clinical application.…”
Section: Resultsmentioning
confidence: 99%
“…Further, we found that plasma Hcy levels were higher in VaD patients than in AD patients. In our meta-analysis, we included 26 studies (Fekkes et al, 1998;Pollak et al, 2000;Wang et al, 2001;Maxwell et al, 2002;Malaguarnera et al, 2004;Irizarry et al, 2005;Zhang et al, 2005;Guidi et al, 2006;Davis et al, 2007;Galimberti et al, 2008;Kim et al, 2008a;Bi et al, 2009;Hooshmand et al, 2010;Tu et al, 2010;Ferlazzo et al, 2011;Mansoori et al, 2012Mansoori et al, , 2014Piazza et al, 2012;Yesil et al, 2012;Elhawary et al, 2013;Choe et al, 2014;Doody et al, 2015;Madsen et al, 2015;Ma et al, 2017;Soni et al, 2018;Meng et al, 2019;Lanyau-Domínguez et al, 2020;Sutovsky et al, 2020) (21 for Hcy and 13 for folate) that were not included in previous studies. Subgroup analysis by ethnicity revealed that dementia patients in Caucasian and Asian cohorts both had high Hcy levels and low folic acid levels.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-nine articles were assessed in the systematic review and three of those studies could not be included in the MA for reasons shown in ESF Table 4. As a result, the meta-analysis was performed on 46 studies (Al-Rawaf et al, 2021;Arce-Varas et al, 2017;Ayromlou et al, 2018;Balmus et al, 2017;Bermejo et al, 2008;Boccardi et al, 2021;Cervellati et al, 2013;Cervellati et al, 2014a;Cervellati et al, 2014b;Chico et al, 2013;Chmatalova et al, 2017;Dong et al, 2008;Du et al, 2019;Gironi et al, 2011;Gironi et al, 2015;Guidi et al, 2006;Gunduztepe et al, 2020;He et al, 2016;Irizarry et al, 2007;Iuliano et al, 2010;Kim et al, 2013;Lanyau-Domínguez et al, 2020;Lee et al, 2013;Liu et al, 2016;Lopez et al, 2013;Ma et al, 2017;Martin-Aragon et al, 2009;Martinez de Toda et al, 2019;McFarlane et al, 2020;Mota et al, 2015;Mueller et al, 2012;Mufson and Leurgans, 2010;Negahdar et al, 2015;Padurariu et al, 2010;Perrotte et al, 2019;Praticò et al, 2002;Rembach et al, 2013;Rinaldi et al, 2003;…”
Section: Search Resultsmentioning
confidence: 99%